A NEW CUBIC EQUATION OF STATE AND ITS APPLICATIONS TO THE MODELING OF VAPOR-LIQUID EQUILIBRIA AND VOLUMETRIC PROPERTIES OF NATURAL FLUIDS - Duan Z.; Hu J. (My University, 2004)
A cubic equation of state was developed for both pure systems and mixtures in this study. It has only one empirical constant to be evaluated for each component and two constants for each binary. To test its validity, the saturated properties of 22 pure fluids were calculated with the new equation, as compared with the most frequently used or the most recently published cubic equations. The results indicate that the new equation is superior to the previous cubic equations in the overall performance in vapor pressures and saturated volumes. Its overall average deviation of the saturation pressures from experiments is 0.46%, and the maximum deviation is 3.6%. Its average deviation of the liquid volumes from experiments at the reduced temperatures Tr≤0.95 is 2.80%, and that of vapor volumes is 2.2%. Because of the high accuracy of the new equation for saturation pressures, it can be easily extended to binary mixtures for the prediction of vapor-liquid equilibria (both densities and compositions) with a simple mixing rule, as demonstrated by eight binary systems, including an aqueous mixture.